Double Condensation of 3-Coumaranone with Aromatic Carbonyl Compounds Catalyzed by Brønsted Hyperacids - Karima Boussafi; Didier Villemin; Nathalie Bar (Chemistry Proceedings)
Condensation of two molecule of 3-coumaranone with aromatic carbonyl compounds is catalyzed by PFAT under microwave irradiation, new dicoumararan-3-ones are obtained.